A retrospective, matched case-control study of recombinant LH versus hMG supplementation on FSH during controlled ovarian hyperstimulation in the GnRH-antagonist protocol - Chen, Ming-Jer; Yi, Yu-Chiao; Guu, Hwa-Fen; Chen, Ya-Fang; Kung, Hsiao-Fan; Chang, Jui-Chun; Chuan, Shih-Ting; Chen, Li-Yu (Frontiers in Endocrinology, 2022)
Background The role of luteinizing hormone (LH) in controlled ovarian hyperstimulation (COH) requires more evidence for its efficacy. Several studies compared recombinant human LH (r-hLH) or human menopausal gonadotropin (hMG) in combination with recombinant human follicle-stimulating hormone (r-hFSH) but lack the results with GnRH-antagonist protocol and in Asians. Methods This is a retrospective, single-center study inspecting women receiving GnRH antagonist protocol and r-hFSH+hMG or r-hFSH+r-hLH regimen for over five days for COH in the in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycle in Taiwan from 2013 to 2018. The outcomes of IVF/ICSI cycles were analyzed after propensity score matching between the two groups. A subgroup analysis was conducted in cycles in which women underwent their first embryo transfer (ET), including fresh ET and frozen ET (FET). Results With a total of 503 cycles, the results revealed that the r-hFSH+r-hLH group performed better in terms of numbers of oocytes retrieved (r-hFSH+hMG vs. r-hFSH+r-hLH, 11.7 vs. 13.7, p=0.014), mature oocytes (8.7 vs. 10.9, p=0.001), and fertilized oocytes (8.3 vs. 9.8, p=0.022), while other outcomes were comparable. The analysis of first ET cycles also showed similar trends. Although the implantation rate (39% vs. 43%, p=0.37), pregnancy rate (52% vs. 53%, p=0.90), and live birth rate (39% vs. 45%, p=0.19) were not significantly different, the miscarriage rate was higher in the r-hFSH+hMG group than the r-hFSH+r-hLH group (26% vs. 15%, p<0.05) in first ET cycles. The cumulative live birth rate was significantly higher in the r-hFSH+r-hLH group (53% vs. 64%, p=0.02). No significant difference in rates of ovarian hyperstimulation syndrome (OHSS) was observed. Conclusion The results support the hypothesis that the treatment of r-hLH+r-hFSH improves COH clinical outcomes in the IVF/ICSI cycle.